2013
DOI: 10.1002/col.21799
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic adaptation by illuminant matrix products: An alternative to sharpened von kries primaries

Abstract: Previous attempts to predict chromatic-adaptation correspondence have led to a sharpening dilemma-i.e., Von Kries primaries are chosen that do not include in the positive octant all the realizable (x,y) chromaticities. This leads to paradoxical adaptation predictions for the colors that have negative Von Kries coordinates. A solution is proposed here that expresses the asymmetric-matching relation of chromatic adaptation as the product of two matrix transformations, given source illuminant 1 and destination il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The model's inherent simplicity entirely avoids the veritable minefield of conventional chromatic adaptation models including such issues as the relative advantages/disadvantages of different chromatic-adaptation primaries and their effect on color gamut, for example the spectral sharpening or purple problem, and of course the considerable and ever-changing math complexities of Von Kries (e.g., CIE-CAT02) or two-matrix chromatic adaptation transforms. [14][15][16][17] In their place, admittedly, the present model introduces the (relatively minor) complexity of equivalent wavelength for nonspectral hues, which diminishes after initial use.…”
Section: Resultsmentioning
confidence: 99%
“…The model's inherent simplicity entirely avoids the veritable minefield of conventional chromatic adaptation models including such issues as the relative advantages/disadvantages of different chromatic-adaptation primaries and their effect on color gamut, for example the spectral sharpening or purple problem, and of course the considerable and ever-changing math complexities of Von Kries (e.g., CIE-CAT02) or two-matrix chromatic adaptation transforms. [14][15][16][17] In their place, admittedly, the present model introduces the (relatively minor) complexity of equivalent wavelength for nonspectral hues, which diminishes after initial use.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the non‐symmetric matrices proposed by Oleari as new chromatic adaptation models 24‐27 did not assume sharpened primaries or consider Von Kries’ hypothesis, which constitutes an original approach deserving future analyses. It must also be added that the perfect colour constancy assumed by Oleari does not exist in humans (see Fairchild, 20 p. 140), and therefore the influence of different degrees of adaptation must be investigated further in results found using Oleari's approach 24 …”
Section: Colour Differences and Chromatic Adaptationmentioning
confidence: 99%
“…Colour constancy is served by the mechanisms of chromatic adaptation and memory colour (see Fairchild,20 p. 27). By assuming perfect colour constancy, the L OSA ,J,G colour space proposed by Oleari on the basis of OSA-UCS system space was also employed to develop new chromatic adaptation transforms, [24][25][26][27] which are the main components of modern colour appearance models. 3,20 Experimental results showed that the chromaticity of the neutral point is close but not equal to that of the illuminant.…”
Section: Chromatic Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Brill and Oleari have also pointed out that using a pair of transformations that map cone space values into and out of a color equivalency representation can be used to define a CAT . As an example, Brill and Oleari introduced the idea of combining an Oleari MAT with the inverse of an Oleari‐based MAT similar to Eq.…”
Section: Sensor Adjustment Transform Approachesmentioning
confidence: 99%